Higiene Penjamah makanan dan Kontaminasi Escherichia Coli pada Es Teh di Kawasan Jalan Tamansiswa Yogyakarta - Bella Viaril Karimah; Muchsin Maulana (Jurnal Kesehatan dan Pengelolaan Lingkungan, 2026)
Iced tea is one of the most widely consumed ready-to-drink beverages and is often perceived as safe. However, improper handling and sanitation practices may increase the risk of microbiological contamination. Escherichia coli is commonly used as an indicator of fecal contamination and inadequate food hygiene. This quantitative study employed an observational analytic design with a cross-sectional approach. The study population consisted of all permanent and semi-permanent restaurants selling iced tea in the study area, totaling 32 establishments, and total sampling was applied. Primary data were collected through direct observation using a hygiene and sanitation checklist and laboratory examination. Microbiological analysis was conducted using the Most Probable Number (MPN) method at the Environmental Health Laboratory, Faculty of Public Health, Universitas Ahmad Dahlan. Statistical analysis was performed using Fisher’s Exact Test. The results showed that most food handlers had good hygiene practices and most restaurants met sanitation standards; however, 96.9% of iced tea samples were contaminated with Escherichia coli. Statistical analysis indicated no significant association between food handler hygiene and the presence of E. coli (p = 1.000). The high level of Escherichia coli contamination in iced tea suggests that factors other than food handler hygiene, such as raw material quality and environmental sanitation, may play a more dominant role. Comprehensive control measures are therefore required to ensure the safety of ready to drink beverages.